2017
DOI: 10.18325/jkmr.2017.27.3.137
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Correlation between the KL-Grade and Improvement of Knee Pain Treated by Korean Medicine Therapy

Abstract: Objectives The purpose of this study is to compare the effects between the KL-Grade and improvement of knee pain treated by Korean Medicine therapy. Methods 114 patients who received inpatient treatment from July 2014 to May 2017 in the Daejeon Jaseng of Korean Medicine Hospital were divided into 5 groups by the KL-Grade. All patients received a combination of treatment including acupunture, pharmacopunture, herbal medication. They were compared and analyzed on the basis of improvement between measuring Numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…In Korean medicine, acupuncture, herbal medicine, and pharmacopuncture are used in combination to treat knee OA and have been shown to give synergistic effects [22,23]. These Korean medicine treatments are provided as combination therapy, and a previous study of in patients with knee OA have been shown to be effective [24].…”
Section: Introductionmentioning
confidence: 99%
“…In Korean medicine, acupuncture, herbal medicine, and pharmacopuncture are used in combination to treat knee OA and have been shown to give synergistic effects [22,23]. These Korean medicine treatments are provided as combination therapy, and a previous study of in patients with knee OA have been shown to be effective [24].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] . 이에 저자의 이전 연구를 발전시켜 퇴행성 반월상 연골판 손상 환자의 한의학적 치 료 효과에 대한 유의한 결과를 얻었기에 이를 보고하는 바이다 17,18) .…”
unclassified